STUDI ETNOGRAFI: KOMUNIKASI LINTAS BUDAYA PADA MAHASISWA PAPUA DAN NON PAPUA DI UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA - Pramudya Wardhana Indracahya (2023)
Papua is a region of Indonesia that attracts public attention, in terms of language, culture and the problems that arise due to complexity. In order to pursue a higher and more appropriate education, many of its people flock to the capital city of Jakarta. One of the campuses where there are several Papuan students is the Jakarta Pembangunan Nasional 'Veteran' University. However, it turns out that there are differences in communication patterns between Papuan students and non-Papuan students. The purpose of this research is to find out the problems in cross-cultural communication patterns of students at the Jakarta Pembangunan Nasional 'Veteran' University. This research is a qualitative research with an ethnographic approach. There are two sources of data in this study including primary and secondary data sources. Primary data sources were obtained by conducting interviews and observations, while secondary data sources were obtained through literature study. There were five informants in this study who were determined through snowball sampling. The final results found in this study included several differences in communication between Papuan students and non-Papuan students. There are also communication barriers between them such as miss perception, the pronunciation of the standard language from Papuan students, the existence of a play on language and the lack of understanding of non-Papuan students about Papuan life. To minimize these obstacles, Papuan students do a number of things such as being more open to non-Papuan students, seeking information about their surroundings through social media, and opening themselves up more to be able to mingle and learn a lot about Jakarta's culture and language.